2000
DOI: 10.1063/1.126247
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced coherent terahertz emission from indium arsenide in the presence of a magnetic field

Abstract: Articles you may be interested inElectric-field-induced anisotropy of excitonic optical properties in semiconductor quantum dots

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(41 citation statements)
references
References 8 publications
3
37
1
Order By: Relevance
“…Using this assumption, we deduce an average THz power of 40 µW. To our knowledge, this value, supported by the large value of P/P probe , represents the strongest THz signal reported in the literature using a Ti:sapphire oscillator as a pump source (Cai et al 1997, Wu and Zhang 1997, McLaughlin et al 2000, Heyman et al 2001, Andrews et al 2002.…”
Section: Resultssupporting
confidence: 49%
“…Using this assumption, we deduce an average THz power of 40 µW. To our knowledge, this value, supported by the large value of P/P probe , represents the strongest THz signal reported in the literature using a Ti:sapphire oscillator as a pump source (Cai et al 1997, Wu and Zhang 1997, McLaughlin et al 2000, Heyman et al 2001, Andrews et al 2002.…”
Section: Resultssupporting
confidence: 49%
“…This work builds on the large body of literature related to terahertz emission from InAs. [5][6][7]11,13,20,21 We have observed a temperature-induced polarity reversal of the terahertz radiation from both p-InMnAs and n-InMnAs, in contrast to what has been previously observed in p-InAs. 6,7 We attribute the observed polarity reversal of the terahertz radiation to the competition between two oppositely directed sources of photoinduced current: the surface-fieldinduced current and the photo-Dember effect.…”
contrasting
confidence: 51%
“…[5][6][7][8][9][10][11] In particular, magnetic-field-induced enhancement of terahertz radiation from nonmagnetic semiconductor surfaces has been investigated thoroughly. [11][12][13][14][15][16] Recently, terahertz emission from ferromagnetic metal films 17,18 and from the dilute ferromagnetic semiconductor GaMnAs ͑Ref. 19͒ have also been demonstrated.…”
mentioning
confidence: 99%
“…McLaughlin et al [145] reported a quadratic dependence of the THz emission on magnetic field up to 3 T. Beyond 3 T, Ohtake et al [146] demonstrated that the radiated THz power saturates at 4 T, decreases to a minimum at 6 T, and increases again at 14 T.…”
Section: Inas and Other Narrow-gap Semiconductorsmentioning
confidence: 99%